Efektivitas Konseling Kelompok Dengan Teknik Body Movement And Exaggeration Untuk Meningkatkan Motivasi Pada Anak Di Panti Asuhan Al-Kahfi Kecamatan Bukit Kecil Kota Palembang - Sela Ayu Puspita; Kusnadi Kusnadi; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
This study examines the "Effectiveness of Group Counseling with Body Movement Techniques and Exaggeration to Increase Motivation in Children at the Al-Kahfi Orphanage, Bukit Kecil District, Palembang City". This study aims: first, to determine the level of body movement of children at the Al-Kahfi Orphanage after and before applying body movement and exaggeration techniques. Second, to find out the Effectiveness of Group Counseling with Body Movement and Exaggeration Techniques to Increase Motivation in Children at the Al-Kahfi Orphanage, Bukit Kecil District, Palembang City. This study used a quantitative approach and pre-experimental methods, with a population of 20 children with a sample of 7 children using probability sampling. Data collection techniques using questionnaires, observation and documentation. Data analysis techniques through the Wilxocon test with the help of the SPSS version 23 window form program. The results showed that the first was in a high level obtained from the results of the frequency of 7 respondents and 20 statement items with details of 2 children in a low state with a proportion of 28.6%, 5 people in a high state with a proportion of 71.4%. Second, Asymp.sig (2-tailed) has a value of .004. The value of .004 <0.05 means that poetry that Ha is accepted and Ho is rejected means that there is a difference in the results of the Pretest and Posttest. So it was concluded that group counseling with Body Movement and Exaggeration techniques was effective for increasing motivation in children at the Al-Kahfi Orphanage, Bukit Kecil District, Palembang City.